Impact of Sample Preparation Methods on LC-MS/MS Analysis of Molecular Targeted Drugs - Tanaka, Yusuke; Araki, Takuya; Yashima, Hideaki; Yamamoto, Koujirou (Indonesian Journal of Pharmaceutics, 2025)
The therapeutic efficacy of molecular targeted drugs (MTD)s and the risk of certain adverse drug effects are closely related to their blood concentrations, highlighting the importance of optimizing dosage based on therapeutic drug monitoring. In this study, we compared four pretreatment methods for the analysis of 15 MTDs by LC-MS/MS: protein precipitation (PPT), solid-phase extraction (SPE) using a reversed-phase (RP) column, SPE using a mixed-mode cation-exchange RP column, and supported liquid extraction (SLE), and evaluated their effects on recovery rates and matrix effects. While PPT showed high recovery rates (>80%) for 8 out of 15 compounds, certain highly polar MTDs exhibited significant peak intensity decreases with repeated analyses, indicating potential issues with ion suppression due to impurities. SPE using a reversed-phase column (HLB) resulted in low recovery rates for 12 out of 15 compounds. In contrast, SPE using an MCX column yielded high recovery rates (>80%) for 14 out of 15 compounds but exhibited substantial matrix effects for 9 out of 15 compounds (matrix factors >2). Addressing these matrix effects required sample dilution, and achieving higher sensitivity would necessitate extensive method adjustments tailored to each compound. SLE demonstrated the most favorable results, with the largest number of compounds showing acceptable recovery rates and minimal matrix effects. In conclusion, these findings, based on standard protocols from product manuals, suggest that while method optimization could improve performance for specific compounds, SLE appears to be the most suitable first-choice pretreatment method for the LC-MS/MS analysis of MTDs due to its balance of recovery and matrix effect control.